Feedback assessment of the healthcare providers of the tertiary private hospitals in Las Pinas City as to the case rate implementation. - Alarcio-Diesmos, Diovida D.
It has been two years now since the implementation of this case rate payment as the new PhilHealth Insurance Corporation payment scheme to all accredited hospitals in the country. Initially, with the 23 conditions wherein eleven (11) of which are medical and the rest are the twelve (12) surgical procedures. Case rate payment is an internationally accepted payment mechanism that serves to package payment for health interventions. It is beneficial, it is much simpler to administer, and it potentially is more transparent in terms of prices for interventions. Through this mechanism, healthcare providers and members will be able to predict how much PhilHealth would be paying for each of the services provided. Moreover, Case Rates improve the Turn Around Time (TAT) for claims processing and payment to providers in order to achieve better cost-efficiency for PhilHelath and faster claim reimbursements for accredited providers and members. This is also in consonance with the Government's thrust to attain Universal Health Coverage, PhilHealth has embarked on continuous improvement of member benefits to be consistently responsive to ever-changing demands.
Management study (MHA)--University of the Philippines Manila, 2013
Keywords: Health insurance; PhilHealth claims